2015
DOI: 10.1021/acs.biomac.5b00941
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Engineered Nanomicelles Loaded with 3,4-Difluorobenzylidene Curcumin for Targeted Killing of CD44+ Stem-Like Pancreatic Cancer Cells

Abstract: Cancer stem-like cells (CSLCs) play a pivotal role in acquiring multidrug resistant (MDR) phenotypes. It has been established that pancreatic cancers overexpressing CD44 receptors (a target of hyaluronic acid; HA) is one of the major contributors for causing MDR. Therefore, targeted killing of CD44 expressing tumor cells using HA based active targeting strategies may be beneficial for eradicating MDR-pancreatic cancers. Here, we report the synthesis of a new HA conjugate of copoly(styrene maleic acid) (HA-SMA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 68 publications
5
86
0
Order By: Relevance
“…The observed results may be attributed to overexpression of comparatively more CD44 receptors in MiaPaCa-2 cells, which allow more amount of CDF delivered by the HA conjugated formulation (HA-PAMAM-CDF) within the cells and displayed better cell killing. Our results are in agreement with reported literature[5,26].…”
supporting
confidence: 94%
“…The observed results may be attributed to overexpression of comparatively more CD44 receptors in MiaPaCa-2 cells, which allow more amount of CDF delivered by the HA conjugated formulation (HA-PAMAM-CDF) within the cells and displayed better cell killing. Our results are in agreement with reported literature[5,26].…”
supporting
confidence: 94%
“…Its anti-cancer activity is operated through modulation or inhibition of multiple molecular pathways [37]. Furthermore, during the past few years, a number of studies have suggested that Curcumin may have direct or indirect influence on CSC self-renewal pathways, including Wnt/b-catenin, sonic hedgehog, and Notch [3840]. Another important property is that, unlike other known chemotherapeutic compounds, Curcumin does not cause any damage to normal cells [41].…”
Section: Resultsmentioning
confidence: 99%
“…These combined data suggest that micelles utilize the interaction of HA with CD44 receptors to enter the cytosol via receptor-mediated endocytosis [50]. Similar HA blockade studies by other groups have repeatedly confirmed this finding [5153]. …”
Section: Ha-based Micelles As a Trojan Horse For Cancer Therapymentioning
confidence: 56%
“…Free CDF showed a high level of toxicity to pancreatic cancer cells in a MTT assay, and this potency was further increased by targeted delivery in the HA nanomicelle formulation. By comparing targeted HA-SMA-CDF micelles with nontargeted SMA-CDF micelles, the authors found that there was an increased cellular uptake and in vitro carcinoma toxicity resulting from conjugation with HA [53]. Their results indicate a potential for targeted treatment of CD44-expressing pancreatic CSCs, which are known to contribute to the resistance of a tumor to conventional cancer therapy [53,70,71].…”
Section: Cancer Specificity and Toxicitymentioning
confidence: 99%
See 1 more Smart Citation